Awareness regarding measles –rubella campaign in parents of school going children of slum population: A cross-sectional study - Dr. Harshwardhan M, Adishri M, Dr. Komal M, Dr. Ajay M, Dr. Sripad T (South Eastern European Journal of Public Health, 2025)
Measles and rubella are among the most infectious diseases with similar symptoms in humans. Parental knowledge and attitudes toward both disease and vaccinations are known to influence vaccine uptake, contribution of these factors toward vaccination rates in slum populations has not yet studied. Aim- The aim of the study is to evaluate the awareness regarding measles –rubella campaign in parents of school going children of slum population. Objectives: The objectives of the study are to assess the knowledge and practices regarding measles-rubella diseases in the parents of school going children of slum populationand to create awareness regarding measles-rubella campaign in the slum population. Methods: A cross-sectional study was conducted in municipal schools where knowledge regarding awareness of measles –rubella was assessed with the help of validated questionnaire. Results: After imparting knowledge regarding (MRC) post test scores were found to bestatistically significant (p<0.05) as compared to pre-test scores. Conclusion: The results of our study have clearly demonstrated that after creating awareness regarding measles –rubella campaign in parents of school going children’s concepts about campaign drive became much clearer for them.